2013
DOI: 10.1021/ja402848c
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Product Inhibition in Catalysis of the Intramolecular Schmidt Reaction

Abstract: A method for carrying out the intramolecular Schmidt reaction of alkyl azides and ketones using a substoichiometric amount of catalyst is reported. Following extensive screening, the use of the strong hydrogen bond donating solvent hexafluoro-2-propanol was found to be consistent with low catalyst loadings, which range from 2.5 mol% for favorable substrates to 25 mol% for more difficult cases. Reaction optimization, broad substrate scope, and preliminary mechanistic studies of this improved version of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 57 publications
0
50
0
Order By: Relevance
“…We were able to achieve a moderate yield of cyclic lactam (±)- 6 with excess ketone, Lewis acid and longer reaction times. While this research was underway, Aubé et al proposed that an unfavorable catalyst–product interaction results in product inhibition, thus deterring the progress of the reaction under catalytic conditions, which leads to the use of excess Lewis acid in super stoichiometric amounts [3738]. They reported that the use of hexafluoroisopropanol (HFIP) can reduce the Lewis acid requirement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to achieve a moderate yield of cyclic lactam (±)- 6 with excess ketone, Lewis acid and longer reaction times. While this research was underway, Aubé et al proposed that an unfavorable catalyst–product interaction results in product inhibition, thus deterring the progress of the reaction under catalytic conditions, which leads to the use of excess Lewis acid in super stoichiometric amounts [3738]. They reported that the use of hexafluoroisopropanol (HFIP) can reduce the Lewis acid requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Upon careful examination of the spectral data and on the basis of the recent results from the Aubé group [3738], the initially anticipated 1,3-substituted structure was revised to 1,2-substituted cyclopentenoid lactams (±)- 6 , as drawn in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
“…(C) Overcoming product inhibition through proton shuffling with hexafluoroisopropanol (HFIP) solvent. 5 …”
Section: Figurementioning
confidence: 99%
“…1,5 However, the observation that turnover frequency and number were strongly correlated with temperature supports the idea that heat may be underexplored in overcoming product inhibition in catalysis.…”
mentioning
confidence: 90%
See 1 more Smart Citation